Pengaruh Kualitas Layanan, Kepercayaan dan Kemudahan Mobile Banking Muamalat Din Terhadap Kepuasan Nasabah pada Bank Muamalat Indonesia KCU Medan Baru - Dina Nudia Ahsanah; Muhammad Syahbudi; Ahmad Syakir (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine and analyze the effect of service quality, trust and convenience of Muamalat DIN mobile banking on customer satisfaction at Bank Muamalat Indonesia KCU Medan Baru. The type of research used is quantitative research. The number of samples in this study was 96 customers with the determination of the sample size using the Lemeshow formula. Data analysis used is multiple linear regression analysis using SPSS. The results of this study indicate that simultaneously and partially service quality, trust and convenience have a positive and significant effect on customer satisfaction. And based on the coefficient of determination, the independent variable is able to influence the dependent variable by 52.9%.